2014
DOI: 10.1186/1471-2393-14-97
|View full text |Cite
|
Sign up to set email alerts
|

Drinking before and after pregnancy recognition among South African women: the moderating role of traumatic experiences

Abstract: BackgroundSouth Africa has one of the world’s highest rates of fetal alcohol spectrum disorder (FASD) and interpersonal trauma. These co-occurring public health problems raise the need to understand alcohol consumption among trauma-exposed pregnant women in this setting. Since a known predictor of drinking during pregnancy is drinking behavior before pregnancy, this study explored the relationship between women’s drinking levels before and after pregnancy recognition, and whether traumatic experiences – childh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 44 publications
4
41
1
Order By: Relevance
“…The influence of ACEs on perceived stress (Nelson et al, 2010) and anxiety (Agrati et al, 2015; Buist, Gotman & Yonders, 2011) during pregnancy may contribute to use of alcohol as a coping mechanism (Choi et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of ACEs on perceived stress (Nelson et al, 2010) and anxiety (Agrati et al, 2015; Buist, Gotman & Yonders, 2011) during pregnancy may contribute to use of alcohol as a coping mechanism (Choi et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…While we were interested in controlling for prenatal alcohol use to better understand the independent relationship between ACEs and alcohol use during pregnancy, it is important to note that pre-pregnancy alcohol use may actually moderate the relationship between ACEs and alcohol use during pregnancy. A recent longitudinal study in South Africa found that women with a history of childhood trauma (physical abuse, sexual abuse, emotional abuse, and neglect) increased their risky alcohol consumption after becoming pregnant regardless of their pre-pregnancy alcohol use levels (Choi et al, 2014). The cultural context of using alcohol during pregnancy in South Africa is likely different from that in the U.S., but this study highlights the need for prospective studies with adequate power to explore the complex relationships between ACEs, prenatal alcohol consumption, and alcohol use during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women who were more advanced in their pregnancy tended to have lower levels of depression. Recent research in this setting has revealed that pregnancy recognition can be a stressful and often undesirable experience (Choi et al, 2014; Watt et al, 2014), so it is possible that women who are further along in their pregnancy may have more time to reconcile with their pregnancy status and adjust to the stressors brought on by pregnancy. Notably, however, one in four women in the sample did present with comorbid antenatal depression and PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…The Revised Conflict Tactics Scales (CTS-2) was used to assess IPV in the current relationship. The CTS-2 has good cross-cultural reliability and has been used in low-resource settings (Nayak et al 2010; Shamu et al 2011; Kastello et al 2015) and in South Africa (Dawes et al 2006; Choi et al 2014). A short form of the U.S. Household Food Security Survey Module (HFSSM) measured inadequacy of food each month, frequency of going hungry, and not having money to buy enough food for the individual or their household in the preceding 6 months (Blumberg et al 1999).…”
Section: Methodsmentioning
confidence: 99%